Effect of Sports in Self-Control Self-Management Levels of Students - Mehmet Özdemir; İhsan Kuyulu; Hakkı Ulucan; Enes Beltekin (Türk Spor ve Egzersiz Dergisi)
The study was conducted to examine the effect of sports on students' self-control and self-management levels. The research group totally consists of 277 people, 125 of them are female and 152 of them are male, studying in the School of Physical Education and Sports in Bingol University in the 2018-2019 academic year. In order to gather data for the purpose of the research, "Self-Control-Self-Management Scale-SCMS" was used. The students participating in the research were asked personal information questions regarding their demographic characteristics. The research was carried out in SPSS 22 statistical package program and the significance level was taken as 0.05. For testing whether the collected data show normal distribution, the normality of the distributions (Kolmogorov-Smirnov) and then skewness and kurtosis tests were examined. According to the test results, double comparisons are Mann Whitney-U, and multiple comparisons are Kruskal Wallis analysis. According to the answers given by the students participating in the research, the self-assessment and self-empowerment levels of the students who are doing licensed sports are significantly higher, female students are more self-confident in the activities that need to be done, and the self-management-control of the students engaged in individual sports levels were determined as higher.